Kazakh translators of the Semirechensk oblast - Abdrakhim, M. (KSU publ., 2020)
This article discusses the activities of Kazakh translators who served in the administration structure of the Semirechensk region. The author examined the positions of regional officials on Kazakh translators, studied the social origins of local translators, their salaries and the motives for joining the civil service. Also, this article analyzes the image of Kazakh translators who served in the regional administration.
Keywords: translator; Semirechensk oblast; kazakh officials; regional administration; rank; position; kazakh translators